Aero-medical aspects of inadvertent operation of ejection seat firing handle: A field study - Murtaza; Vijaya Vardhan Indluru (Indian Journal of Aerospace Medicine, 2026)
Inadvertent firing of an ejection seat handle is a flight safety hazard that may lead to accidental ejection on the ground or in the air. An incident of unintended firing of the ejection handle due to fouling of the flying clothing with the ejection handle on the ground in a trainer aircraft was reported, which led to a study from an aero-medical point of view that looked into various aspects such as anthropometric issues, generation of force by body movement, seat design, and harness fouling with ejection handle. Ten aircrew subjects were selected based on various anthropometric parameters and divided into four groups: Short, tall, thin, and overweight. The trial and assessment were conducted in two stages: first, in an ejection seat bay within a simulated environment, and second, in an actual cockpit of a parked aircraft. Various aero-medical aspects, such as the probability of specific anthropometric parameters causing fouling, seat and harness design, strapping procedure, and the impact of seat modification, were studied. Findings revealed that the design of the negative G strap stiffener, combined with a lack of vigilance while strapping, has the potential to cause entanglement of the stiffener with the ejection handle, which may lead to inadvertent operation of the firing handle. No specific anthropometric parameter was found to be relevant to the increased risk. Earlier modifications of the seat did not appear to influence the possibility of fouling. In this fighter trainer cockpit, the flexibility of the ejection handle and the sliding aspect of the negative G strap stiffener create a dynamic link that, when combined with the strapping procedure, can lead to fouling of the handle with flying clothing. This can cause inadvertent firing of the ejection handle. Design modification of the negative G assembly stiffener, along with modification of the Pilot Orders, has been suggested to preclude inadvertent fouling with the ejection firing handle.